2004
DOI: 10.1117/12.541537
|View full text |Cite
|
Sign up to set email alerts
|

Endmember selection techniques for improved spectral unmixing

Abstract: Hyperspectral imaging provides the potential to derive sub-pixel material abundances. This has significant utility in the detection of sub-pixel targets or targets concealed under canopy. The linear mixture model describes spectral data in terms of a basis set of pure material spectra or endmembers. The success of such a model is dependent on the choice and number of endmembers used and the unmixing process. Endmember spectra may come from field or laboratory measurements, however, differences between sensors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…It is generally recommended to validate the N-FINDR results against approaches like the PPI. After positive validation results, the N-FINDR algorithm has significant advantages over manual endmember retrieval, or the usage of reference spectra of surface material as discussed in Howes et al (2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally recommended to validate the N-FINDR results against approaches like the PPI. After positive validation results, the N-FINDR algorithm has significant advantages over manual endmember retrieval, or the usage of reference spectra of surface material as discussed in Howes et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…As a constraint, all three abundance values (F i ) have to be >0 and <1. This is known as the non-negativity constraint in previously published literature (Howes et al 2004). Additionally, the sum of the fractions has to be one (sum to one constraint; Howes et al 2004).…”
Section: Spectral Unmixingmentioning
confidence: 98%
See 1 more Smart Citation
“…bad pixels) as endmembers. Indeed Howes et al (2004) reported that convex-based endmember extraction methods were susceptible to outliers since only a single spurious pixel can significantly alter the endmember simplex [21]. Outliers may result for example from noise or atmospheric effects in the data.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this assumption is met is in part a function of the nature of the scene (spatial arrangement of targets) and the spatial resolution of the imagery. In the case of SMACC, N-FINDER, VCA, SGA and Max-D, one pixel (the most extreme pixel) is selected to represent one endmember and thus these methods suffer from the inherent sensitivity of convex geometry to outlier pixels [21]. Although principal component analysis (PCA), minimum noise fraction transform (MNF) and singular value decomposition (SVD) can be applied to the data prior to the endmember extraction to minimize the impact of noise [14, 28], these can also result in the loss of detection of useful endmember pixels characterized by subtle spectral detail.…”
Section: Introductionmentioning
confidence: 99%